Tinnitus in children: an uncommon symptom?. Issue 8 (6th April 2010) - Shetye, A; Kennedy, V
Abstract : Tinnitus in children is regarded as an uncommon problem rarely noted by general paediatricians. Its reported prevalence varies from 12% to 36% in children with normal hearing thresholds and up to 66% in children with hearing loss and approximately 3–10% of children have been reported troubled by tinnitus. Some children do not spontaneously complain of it, but may demonstrate behavioural problems at school and home. A careful history, in conjunction with clinical findings, should guide the appropriate management approach. Even very young children are able to provide insights into what troubles them allowing children's thoughts and fears regarding this symptom to be addressed. We review the available literature on the nature and impact of tinnitus and as guidelines for this do not exist, suggest a pragmatic approach to the management of tinnitus in children. Children with troublesome tinnitus, however, should be referred on to a paediatric audiology department for further investigation and management.